(untitled) (CAHIERS MAGELLANES-NS, 2024)
Technology has come to play a significant role in the area of development of newer modes of payment and settlement. The Covid -19 pandemic forced many people to use the digital payment systems. Digital payments has been the predominant mode of e-banking in India with the internet offering itself as a new delivery mechanism for the banks in reaching the customer. In India to become , cashless economy takes long time to develop it after proper implementation and help the people to understand the concept of cashless transaction to build faith in the digital transaction, it can be achieved in short span of time. The introduction of many digital payment applications to the smartphone users is convenient for most of people with the introduction of innovative online payment service providers in India such as PayPal India, PayUmoney, Paytm, CCAvenue, Razor pay, Instamojo, cash free, EBS. A user or customer makes payment instantly from anywhere and anytime without physical presents. With the growing number of people who are been increasing pressured for time, online utility bill payment has become a graceful solution for the consumers with busy life styles. Through online payment of utility bills, consumers are able to save time, hassle and therefore make their lives much easier. Although online utility bill payment has become one of the fastest growing trends in the world particularly in India. This study will highlight the most preferable utilities of sample respondents have the ability to pay their bills through online by giving customer satisfaction to provide 24/7 payments at any time on any device.